Rapid Antigen Diagnostic Test for Quick Detection of Streptococcal Pharyngitis in Pediatric Age Group - Ali, Mehak (International Journal of Pathology, 2022)
Background: Streptococcus pyogenes is one of the leading causes of acute tonsillopharyngitis across the globe. The inappropriate routine of the antibiotics has steered towards the prevalence and growth of antibiotic resistant bacteria which are becoming virulent pathogens. Misdiagnosis of many infectious diseases, such as streptococcal pharyngitis caused by Streptococcus pyogenes has led to inappropriate use of antibiotics. The symptoms of streptococcal and viral pharyngitis usually similar, this makes the accurate diagnosis by clinical assessment very difficult. The standard methods used for the diagnosis of S. pyogenes include the clinically approved Centor-McIsaac or Modified Centor scoring, Rapid Streptococcal Antigen Detection Test (RADT) and the culture. However, these methods have not been validated in our setup. Objective: To evaluate the efficiency of Rapid Streptococcal Antigen Detection Test (RADT) method for identification of Group A beta hemolytic Streptococcus (GABHS) and comparing its results with that of throat culture. Material and Methods: It was a cross sectional study carried out at the department of Microbiology, Army Medical College Rawalpindi (National University of Medical Sciences) Pakistan and department of pediatrics Military Hospital Rawalpindi from April 2017 to April 2018. The subject of this study was the patients of pediatric age group from 1 year to 15 year old attending Military Hospital Rawalpindi with complains of sore throat. The clinical assessment was done according to Modified Centor criteria and two throat swabs were taken; one was use for Rapid antigen detection test (RADT) assessment and other for throat culture. The results of Rapid antigen detection test (RADT) were compared with throat culture results. And sensitivity, specificity, positive and negative predictive values were determined. Results: Two hundred and seventy children (having mean age of 5.2 years ± 3.1 SD) were considered in the research. The sensitivity and specificity of Rapid antigen detection test came out to be 41.2 % and 99.0 %, respectively. And positive predictive value was 93.3% [95% CI: 73.2%-100%], whereas negative predictive value was 83.3% [95% CI; 81.6 %-84.8 %]. Conclusion: This concluded that Rapid Antigen Detection Test although have high specificity but low sensitivity, are a significant step forward in the diagnosis and management of sore throat.